Business Plan « Feed processing » by Boqa Shuta Shaya CBBP and sheep fattening cooperative in Bonga, Ethiopia - Rudiger, Udo; Wamatu, Jane; Ekule, Muluken (International Center for Agricultural Research in the Dry Areas, 2022)
The objective of the project is to produce valuable compound feed by a farmer cooperative in Bonga, valorizing their own agricultural production. The farmer cooperative uses local available feeds which are not prepared as compound feed and concentrates as well as ingredients imported to fatten their sheep. Through the production of their own compound feed using a feed-producing chain, animals will gate a compound feed from locally available feed resources options and production costs will be reduced, and income increased. Several basic arguments support the realization of such a project: 1. The lack of forage resources in several regions of the country. Shortage of local animal feed sources and high prices of imported feed 2. Improve feed quality as imported concentrates are often of poor quality 3. The very advantageous cost of the feed produced by the unit 4. Provide inexpensive and quality feed in times of shortage of fodder resources or when they are very costly or interrupted in the local market. 5. Need to create employment for youth and women